Perbandingan Kualitas Citra Radiograf Kepala Menggunakan Grid dan Tanpa Grid pada Computed Radiografi - Rini Hatma Rusli; Ira Sandi Tunny; Maritje S. J. Malisngorar; Akhmadi Akhmadi; Yohannes Hursepunny (Pusat Riset dan Inovasi Nasional, 2022)
One factor that plays an important role in the quality of radiodiagnostic examination results is radiographic contrast. When examining thick objects, radiographic contrast will decrease as a result of the large amount of scattered radiation originating from the object and reaching the film. To obtain optimal radiographic contrast on thick objects such as the head, it can be done in various ways, including using a grid. The grid is a tool that functions to absorb scattered radiation but can still transmit primary radiation. Examination of the head is done to get the head radiograph and to determine any abnormalities or diseases of the head. This examination was performed using the grid and without grid to compare the better results of radiographs. Radiographs results were obtained using processing film, Computed Radiography (CR). This research used descriptive study conducted at Hospital Tk. II Pelamonia Makassar on January 2020. Based on the results of the research which conducted for examination of the head using grid and without grid on CR cassette obtained that the result of radiograph examination of the head using a grid was better.